(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
Study of changes of free proline content in connection with organ formation processes of two potato sorts has shown that these processes are accompanied by the increase of free proline content in all organs of plants within different quantitative limits. The comparison of sensability of various organs of potato to the break of organism equalized state has shown the significant differences between organs of both middle and late ripe sorts. When transition to the tuberization took place the free proline content reached its maximum in stolons for both sorts, especially for the late ripe sort. This fact indicates that among all organs the stolons are the most sensible to the break of equalized state.